(untitled) (Functional Plant Breeding Journal, 2021)
This article seeks to understand the system of relationships between fundamental rights, Human Rights and education in the context of Higher Education. Through bibliographical research, it is intended to highlight the punctuality of these articulations in the educational environment and the moral and pedagogical basis that rights have on the agents of the knowledge production process. Thus, the feeling of exercising citizenship in these spaces of knowledge production can bring clues to the educational regime as a trainer of professionals.